1999
DOI: 10.1021/tx990048u
|View full text |Cite
|
Sign up to set email alerts
|

Site-Specific Synthesis of Aflatoxin B1 Adducts within an Oligodeoxyribonucleotide Containing the Human p53 Codon 249 Sequence

Abstract: This work describes the preparation of the cationic trans-8, 9-dihydro-8-(N7-guanyl)-9-hydroxyaflatoxin B(1) ((AFB)G) adducts at the positions corresponding to G(746) or G(747), within the oligodeoxyribonucleotide d(GGAGGCCT) containing the codon 249 sequence (underlined) of the p53 gene, using DNA triplexes to target adduction at the desired site. This approach enabled the successful preparation and purification of sufficient quantities of d(GGAG(AFB)GCCT) for NMR structural studies, using only standard phosp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2000
2000
2011
2011

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 54 publications
0
4
0
Order By: Relevance
“…A shortcoming of the method is that methylation also occurs on O 6 of guanine, N 3 of adenine, and other sites. Direct alkylation has been used successfully for preparation of oligonucleotides containing the AFB-Fapy-dGuo adduct , . The regiospecificity of reactions of aflatoxin epoxide is much higher than that of dimethyl sulfate.…”
Section: Discussionmentioning
confidence: 99%
“…A shortcoming of the method is that methylation also occurs on O 6 of guanine, N 3 of adenine, and other sites. Direct alkylation has been used successfully for preparation of oligonucleotides containing the AFB-Fapy-dGuo adduct , . The regiospecificity of reactions of aflatoxin epoxide is much higher than that of dimethyl sulfate.…”
Section: Discussionmentioning
confidence: 99%
“…, AFB 1 - exo -8,9-epoxide 1518. The exo -epoxide interacts with DNA predominantly through binding to guanine residues at N7 position forming trans -8,9-dihydro-8-(N7-guanyl)-9-hydoxyaflatoxin B 1 (AFB 1 -N7-Gua) adducts, although small quantities of the corresponding adenine adducts can also be formed 15, 16, 1921. Alternatively, the highly reactive AFB 1 - exo -8,9-epoxide can be detoxified through conjugation with glutathione catalyzed by glutathione S -transferase, or conversion to AFB 1 -dihydrodiol catalyzed by microsomal epoxide hydrolase ( reviewed in 8, 9, 18).…”
Section: Introductionmentioning
confidence: 99%
“…The principal site of covalent interaction of the epoxide with DNA is the N7 atom of guanine, leading to a positively charged adduct formation, Aflatoxin-DNA, which upon hydrolysis forms 8,9-dihydro-2-(guan-7-yl)-3hydroxy-aflatoxin. [18][19][20][21][22][23] Unlike aflatoxins B 1 and G 1 , aflatoxins B 2 Scheme 1 and G 2 show much lower carcinogenicity, which has been mainly associated to the absence of the furan ring unsaturation. 24 Recently, theoretical studies clearly demonstrated that aflatoxins, specially the B 1 form, can be responsible for phototoxic reactions involving the formation of reactive oxygen species.…”
Section: Introductionmentioning
confidence: 99%